2006
DOI: 10.1111/j.1460-9568.2006.04679.x
|View full text |Cite
|
Sign up to set email alerts
|

Firing cell repertoire during carbachol‐induced theta rhythm in rat hippocampal formation slices

Abstract: One hundred and seven cells were recorded extracellularly in hippocampal formation (HPC) slices during carbachol-induced theta. The data obtained provided evidence of a population of HPC neurons which, when activated cholinergically, participate in the generation of in vitro theta. The activity patterns of in vitro recorded theta-related cells were shown to be similar to those of theta-related cells recorded in vivo and cells recorded in vitro during cholinergically induced theta, and non-theta intervals were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 43 publications
(74 reference statements)
1
30
0
Order By: Relevance
“…Results obtained with a cholinergic agonist favor this latter idea. Carbachol increases rhythmic neuronal firing in hippocampal slices (Colgin et al, 2003, Konopacki et al, 2006) and induces BDNF via AMPAR-independent mechanisms (Lauterborn et al, 2003). Carbachol down-regulated GluR1 and GluR2 mRNA and protein levels in field CA1 with the same magnitude and time course as did the ampakine CX614.…”
Section: Discussionmentioning
confidence: 99%
“…Results obtained with a cholinergic agonist favor this latter idea. Carbachol increases rhythmic neuronal firing in hippocampal slices (Colgin et al, 2003, Konopacki et al, 2006) and induces BDNF via AMPAR-independent mechanisms (Lauterborn et al, 2003). Carbachol down-regulated GluR1 and GluR2 mRNA and protein levels in field CA1 with the same magnitude and time course as did the ampakine CX614.…”
Section: Discussionmentioning
confidence: 99%
“…According to our previous studies (Konopacki et al, ; Kowalczyk et al, ,b), some neurons were also classified as gating cells if they met one of the following criteria: (i) the cell discharges occurred precisely in the beginning and at the end of each theta epoch (gating cell A); (ii) the cell began to discharge just before the transition from non‐theta interval/LIA into the theta epoch (gating cell B); (iii) the cell began to discharge just after the transition from the theta epoch into non‐theta interval/LIA (gating cell C).…”
Section: Methodsmentioning
confidence: 99%
“…The production of theta oscillations in a brain slice preparation takes place in the presence of bath perfusion with cholinergic agonists (Kazmierska et al, 2012;Konopacki et al, 1987Konopacki et al, , 2006Konopacki, 1996Konopacki, , 1998Kowalczyk et al, 2001), or simultaneous perfusion with GABA A and GABA B antagonists (Konopacki, 1998). Konopacki et al (1987) observed that when hippocampal slices are bathed in a solution containing the muscarinic agonist carbachol, short bursts of field oscillation at 4-15 Hz occur intermittently.…”
Section: Discussionmentioning
confidence: 98%
“…Numerous studies carried out in vivo and in vitro have demonstrated that the appearance of theta rhythm requires a certain level of excitation of local neuronal networks (Bland and Colom, 1993;Bland, 2008;Cobb et al, 1995;Konopacki et al, 2006;Konopacki and Gołębiewski, 1993;Yoder and Pang, 2005). Many years of research conducted with the use of models of HPC slice preparations have allowed us to determine the specific role of the cholinergic (Kazmierska et al, 2012;Konopacki et al, 1987Konopacki et al, , 2006Konopacki, 1998;Kowalczyk et al, 2001) and GABAergic systems (Gołębiewski et al, 1996;Konopacki and Gołębiewski, 1993;Konopacki et al, 1997) in providing the adequate level of neuronal excitation necessary for theta to appear.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation